On combinatorial properties of the semigroups of the fourth order - В. M. Бондаренко; Я. В. Заціха (Науковий вісник Ужгородського університету. Серія: Математика і інформатика, 2017)
In this paper we study combinatorial semigroups of order 4 (up to isomorphism and duality, their number is 126).